Differences in utilisation of digestible macronutrients between two different size classes of rainbow trout (Oncorhynchus mykiss) - Ruben Groot; Philip Lyons; Johan W. Schrama (Animal Nutrition)
The aim of this study was to investigate whether fish size has an effect on the utilisation efficiency of digestible protein, digestible fat and digestible carbohydrates (Carb) for energy gain in rainbow trout. Four different diets ranging in protein, fat and Carb were fed to two size classes of rainbow trout, 30 to 75 g and 92 to 214 g, at three different feeding levels (12, 8 and 4 g/kg0.8 per day). This led to 24 treatments with 2 replictes (tanks). Tanks contained 36 fish for the 30 to 75 g fish and 24 fish for the 92 to 214 g fish. Faeces was collected for the determination of the digestibility of protein, fat and Carb. Energy retention was determined from the initial and final body composition. The design of this trial allowed for multiple regression analysis to determine the utilisation efficiency of the different digestible macronutrients for energy gain. By doing so, it was also possible to establish specific net energy (NE) formulae for 30 to 75 g and 92 to 214 g rainbow trout. The results showed that there were differences between the two size classes in the estimated NE formulae and the corresponding partial efficiencies of digestible protein, fat and Carb for NE (kgNE,CP, kgNE,Fat and kgNE,Carb). The kgNE,CP was not different (P = 0.586) between the two size classes (on average 76%), but the kgNE,Fat decreased (P = 0.005) from 82% to 65% in the bigger fish and the kgNE,Carb showed a tendency (P = 0.077) to increase from 55% to 73% in the bigger fish. The findings of this study showed that fish size has an effect on the estimation of net energy in feeds for rainbow trout.